2015
DOI: 10.1089/scd.2014.0533
|View full text |Cite
|
Sign up to set email alerts
|

Immaturity of Human Stem-Cell-Derived Cardiomyocytes in Culture: Fatal Flaw or Soluble Problem?

Abstract: Cardiomyocytes from human pluripotent stem cells (hPSC-CMs) are increasingly used to model cardiac disease, test drug efficacy and for safety pharmacology. Nevertheless, a major hurdle to more extensive use is their immaturity and similarity to fetal rather than adult cardiomyocytes. Here, we provide an overview of the strategies currently being used to increase maturation in culture, which include prolongation of time in culture, exposure to electrical stimulation, application of mechanical strain, growth in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
207
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 235 publications
(216 citation statements)
references
References 164 publications
(283 reference statements)
7
207
0
2
Order By: Relevance
“…Importantly, our hCO constructs were found to be physiologically representative of the native immature human heart. This finding is consistent with the characterization of other hCO constructs, which were also found to be most comparable with the fetal human heart (Veerman et al, 2015). Remarkably, hCOs were able to completely recover cardiac function following cryoinjury, displaying many of the hallmarks of regenerative neonatal heart tissue.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Importantly, our hCO constructs were found to be physiologically representative of the native immature human heart. This finding is consistent with the characterization of other hCO constructs, which were also found to be most comparable with the fetal human heart (Veerman et al, 2015). Remarkably, hCOs were able to completely recover cardiac function following cryoinjury, displaying many of the hallmarks of regenerative neonatal heart tissue.…”
Section: Discussionsupporting
confidence: 88%
“…β-Myosin heavy chain (β-MHC, also known as MYH7), myosin light chain 2v (MLC2v also known as MYL2) and the N2B isoform of titin (TTN N2B) (Opitz et al, 2004) are the dominant isoforms expressed in adult cardiomyocytes. By contrast, alphamyosin heavy chain (α-MHC also known as MYH6), myosin light chain 2a (MLC2a also known as MYL7, and the N2BA isoform of titin (TTN N2BA) are the dominant isoforms expressed during early embryonic development and in standard 2D cultures of hPSC-derived cardiomyocytes (Veerman et al, 2015). qPCR analysis revealed that hCOs had much lower expression of the adult sarcomeric isoforms (β-MHC, MLC2v and TTN N2B) and higher expression of the fetal sarcomeric isoforms (MLC2a), compared with native adult human heart tissue (Fig.…”
Section: Results Hcos Possess Features Of Immature Human Myocardiummentioning
confidence: 99%
“…Typical fetal features that they display include automaticity of beating, depolarized diastolic V m , low ion channel expression, delayed excitation‐contraction coupling and low contractile force (Veerman et al , 2015). Defined culture conditions (Burridge et al , 2014; Ribeiro et al , 2015a, 2015b) can be used to improve the maturation of hPSC‐CMs to reveal hidden disease phenotypes (Birket et al , 2015) or to drive differentiation to chamber‐specific cell populations (Devalla et al , 2015), and drug testing might benefit from their standardization.…”
Section: Limitations In Applicability Of Hipsc‐cm To Large‐scale Drugmentioning
confidence: 99%
“…However, it is important to note that the effects of DNA methylation inhibitors on cardiomyocyte proliferation were observed in immature cardiomyocytes and DNA methylation likely plays diverse roles in regulating cell proliferation at different stages of development. Human ESC-derived cardiomyocytes have been previously characterized to be similar to foetal or embryonic cardiomyocytes (Veerman et al, 2015). While the current results provide supporting evidence for a role of DNA methylation in guiding cardiomyocyte cell cycle shutdown during development, it is unclear whether inhibiting DNA methylation at later stages of development (i.e.…”
Section: Discussionmentioning
confidence: 54%
“…Maturation of human PSC-derived cardiomyocytes is another major barrier in the field (Veerman et al, 2015). The finding that DNA methylation facilitates cardiomyocyte cell cycle arrest and maturation also has important ramifications for the cell therapy field and for disease modelling applications.…”
Section: Harnessing the Dna Methylome For Cardiac Regenerationmentioning
confidence: 99%